STANDAARD BANK CREDIT AGREEMENT BASED ON THE VALUE OF JUSTICE - Sahal Fahmi (International Journal of Law Reconstruction, 2017)
The treaty law is an open system with the principle of freedom of contract as stipulated in Article 1338 paragraph (1) of BW. The freedom provides an opportunity for all parties, including banks to make an agreement in the form of standaard. This standaard agreement is burdensome because there is no bargaining position between the community as a debtor customer with the bank as a creditor. However, such agreement continues in the banking practice. The purpose of this study is to find the factors influencing standaard bank credit agreement on the distribution of credit to the community based on the value of justice. This research uses normative juridical method, with primary-secondary data from the library research. As a result, the bank credit agreement in the form of standaard is still not based on the value of justice because the content is determined unilaterally by the bank, where the debtor's customer does not have bargaining position on some form of agreement used by the bank; application credit agreement and bookkeeping requirements; cash bookkeeping requirements; Deposit book-entry application; application agreement of remittance. In addition, it still has delicacy on the bank credit agreements which are limited by the Banking Act and the Decree, Regulation and Circular of Bank of Indonesia. The legal provision generates the prudent principle of extending the credit to the community, which is famous for the 5 C's (Character, Capacity, Capital, Collateral, Condition). Meanwhile, the Bank Indonesia Regulation stipulates regulation relating to the regulations, prohibitions, institutions, guarantees, and execution of the guarantee objects.